Life stressors and resources as predictors of adolescent suicide attempt - Campbell, Catherine Sandra (University of the Free State, 2012)
The continuing rise in adolescent suicide worldwide constitutes a serious public health challenge. Several environmental and personal factors, such as early losses, discordant relationships, poverty, abuse and other life crises have previously been associated with the rise in adolescent suicides. However, only a few South African studies have investigated the combined occurrence of these factors among the different racial groups. This study investigated the role of gender, race and psychosocial stressors and resources in attempted suicide among 1 033 Grade 11 and 12 learners from schools in the Free State Province, South Africa. A cross-sectional research design was applied. Participants completed a biographical questionnaire and the Life Stressors and Social Resources Inventory, Youth Form. Logistic regression analysis was used to identify stressors, resources and demographic variables that predict attempted suicide among the sample of learners. The findings of the current study suggest that 12.5% of the sample had previously attempted suicide. Being coloured (p ≤ .01) and being female (p ≤ .01) significantly increased the likelihood of attempting suicide. Stressors significantly associated with the increased likelihood of attempting suicide for the whole group were stressors regarding Parents (p ≤ .05), Extended Family (p ≤ .01), Home and Money (p ≤ .05), and Negative Life Events (p ≤ .01). Resources significantly associated with the reduced likelihood of attempting suicide for the whole group were supportive relationships with Parents (p ≤ .01), with Boyfriend/Girlfriend (p ≤ .01) and Positive Life Events (p ≤ .01). These findings highlight the importance of supportive relationships and stable home conditions for the well-being of adolescents. The limitations of this study included an under-representation of black participants in the sample. Furthermore, owing to the cross-sectional design of the study, conclusions cannot be drawn with regard to any causal relationship between demographic variables, life stressors and resources, and attempted suicide. It is recommended that future research studies include factors such as self-esteem and sense of coherence.
Dissertation (M.Soc.Sc. (Psychology))--University of the Free State, 2012
Keywords: Teenagers -- Suicidal behavior; Suicidal behavior; Stress in adolescence; Free State (South Africa); Protective factors; Relationships; Risk factors; Gender; Race; Resources; Life stressors; Adolescent suicide